PERBANDINGAN FUNGSI DAN MAKNA FUKUSHI YANG BERARTI ‘AKHIRNYA’ DALAM NOVEL BOTCHAN KARYA NATSUME SOUSEKI - Suriasih, Ni Luh Gede (Humanis; Volume 10. No 2. Februari 2015, 2015)
This research analyzed the function and meaning of ‘finally’ adverbs in Japanese Language. There are two objects to be analyzed. The first object is to compare the function  of adverb ‘finally’. The second object is to compare the meaning of adverb ‘finally’. When  analyzing these words, there are three steps teken. The first step is collecting the data. The second step is analyzing the data. And the last step is to present the result of the study. The data source was taken from a novel by Natsume Souseki entitle “Botchan”. There are five adverbs of ‘finally’. Toutou, youyaku, tsui ni, yatto, and iyo-iyo.  The result of the study showed that toutou, youyaku, tsui ni, yatto, and iyo-iyo has one functions. Toutou has three meanings and  youyaku, tsui ni, yatto, and iyo-iyo has one meanings.
Keywords: fukushi, toutou, youyaku, tsui ni, yatto, iyo-iyo, verb, adjective